Pandemics, structural crisis and then ¿what? Debates on socioeconomic development, territory, and alternative economies - Pastore, Rodolfo (Cooperativismo & Desarrollo, 2021)
This article analyzes socioeconomical problems and the inequality gaps they generate to highlight the rele-vance of associative processes, as well as economic expansion. This is aimed at strengthening not only the economical dimension, but also the cultural and social one, with a special emphasis in the development of territories. The research is qualitative, reflexive, and analytical, exposing different political, social, and econo-mic positions. Main contributions revolve around the analysis of socioeconomic issues that were raised due the pandemic, from which it is proposed necessary to attend the subject, not only within civil society, but within intergovernmental entities and international institutions. Lastly, a reflection is proposed on the development of territories and the expansion of solidary economies that transform and generate sustainability of life
Keywords: sustainable development; territory development; alternative economies; cooperativism; popular economy